The effectiveness of a proposed study unit in economic geography subject in developing knowledge, skills and attitudes of Omani female students at grade eleven towards entrepreneurship in Muscat Governorate in the Sultanate of Oman - Al-Habsi, Najah Salim Hudeb (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed to explore the effectiveness of a proposed study unit in economic geography subject in developing knowledge, skills and attitudes of Omani female students' at grade eleven towards entrepreneurship in the Governorate of Muscat in the Sultanate of Oman. The researcher implemented a quasi-experimental design in order to achieve the objectives. The participants of the study consisted of (74) female students from grade eleven at the Hail Al-Awamir School for post-basic education. They were divided into two groups: an experimental group which included (37) female students who studied the economic geography subject with thr proposed unit of entrepreneurship and a control group which included about (37) female students who studied the economic geography subject without the proposed unit of entrepreneurship. Data was collected by using knowledge, skills test and attitudes scale. The results of the study showed that the experimental group obtained a total average of (24.8 out of 30) in knowledge test and (43.9 out of 50) in skills test; in return for the control’s average score of (8.7 out of 30) in knowledge test and (5.2 out of 50) in skills test. The attitude scale showed that both the experimental and the control groups had positive attitudes towards entrepreneurship; however, attitudes were positively higher in the experimental group. Also, there were statistically significant differences at the significance level (α = 0.05) between the mean of the two study samples in the knowledge, skill test and the attitude scale in favor to experimental group. The researcher recommended emphasizing the inclusion of entrepreneurship as well as integrating both knowledge and skills in educational curriculum.
Keywords: study unit; entrepreneurship; attitude; effectiveness